Can 3D-CRT meet the desired dose distribution to target and OARs in glioblastoma? A tertiary cancer center experience - Kumar, Narendra (CNS Oncol, 2020)
AIM: The purpose of the study is to perform a dosimetric analysis of the doses received by planning target volume and organ at risks in the postoperative glioblastoma by using 3D-conformal radiotherapy to a total dose of 60 Gy in 30 fractions. MATERIALS & METHODS: All patients received concurrent temozolomide every day, and this was followed by adjuvant temozolomide of 5 days of treatment per month. RESULTS: More than 98% of patients were treated with a dose of 60 Gy. Doses were analyzed for the normal whole brain, tumor volume, as well as all the organs at risk. CONCLUSION: Given the grave prognosis and the limited survival of glioblastoma despite the best treatment available, makes 3D-conformal radiotherapy an equally acceptable treatment option.